2017
DOI: 10.1111/1440-1681.12812
|View full text |Cite
|
Sign up to set email alerts
|

AQP4‐knockout aggravation of isoprenaline‐induced myocardial injury is mediated by p66Shc and endoplasmic reticulum stress

Abstract: Aquaporin 4 (AQP4) is a type of water channel protein that maintains the water balance of cardiomyocytes. However, the physiological role of AQP4 in cardiovascular disease is poorly understood. We wanted to explore whether p66Shc and endoplasmic reticulum stress participates in AQP4 knockout (KO)-mediated cardiac injury. There were two types of mice: AQP4 knockout and wild-type mice. Each type was randomly divided into three groups: Control group, isoprenaline stimulation group (ISO, 1 mg/kg, s.c., 5 days), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…found that p66shc gene‐deficient mice had increased resistance to environmental stressors such as hydrogen peroxide and ultraviolet rays, while their life expectancy increased by 30%. Cheng YS et al demonstrated that upregulation of p66shc increased the production of ROS, aggravated oxidative damage of cells and participated in myocardial injury, corpus cavernosum dysfunction and renal dysfunction . Diabetic nephropathy and ageing have a common mechanism, oxidative stress, and p66shc plays a key role in ageing‐related diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that p66shc gene‐deficient mice had increased resistance to environmental stressors such as hydrogen peroxide and ultraviolet rays, while their life expectancy increased by 30%. Cheng YS et al demonstrated that upregulation of p66shc increased the production of ROS, aggravated oxidative damage of cells and participated in myocardial injury, corpus cavernosum dysfunction and renal dysfunction . Diabetic nephropathy and ageing have a common mechanism, oxidative stress, and p66shc plays a key role in ageing‐related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng YS et al demonstrated that upregulation of p66shc increased the production of ROS, aggravated oxidative damage of cells and participated in myocardial injury, corpus cavernosum dysfunction and renal dysfunction. [5][6][7] Diabetic nephropathy and ageing have a common mechanism, oxidative stress, and p66shc plays a key role in ageing-related diseases. Therefore, there is increasing recognition of the role of p66shc in DN.…”
Section: Introductionmentioning
confidence: 99%
“…[109], FGF12 [110], AQP4 [111], LMOD2 [112], SELENBP1 [113], MB (myoglobin) [114], S100A1 [115], RYR2 [116], GPC5 [117], JARID2 [118], EGFR (epidermal growth factor receptor) [119], FUNDC1 [120], S1PR1 [121], EPAS1 [122] and OSBPL11 [123] genes are a potential biomarkers for the detection and prognosis of HF at an early age. A previous study reported that CALR (calreticulin) [124], BSCL2 [125], PKD1 [126], TMBIM1 [127], CHST15 [128], NAA10 [129], TCF3 [130], CNN1 [131], TAF1A [132], ACAD9 [133], KLHL24 [134], MYOM2 [135], TRIM63 [136] [210] are the key biomarkers in cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, heart morphology appeared largely normal in various AQP deficient mice [58,78,83]. However, upon more close examination, cardiac weight was increased in AQP4 KO mice [79,80], but decreased in AQP1 KO mice [32]. The latter was accompanied by decreased cardiomyocyte dimensions [125].…”
Section: Aqps and Cardiac Contractilitymentioning
confidence: 99%